Developmental and Cytochemical Features of Male Reproductive Organ in Crataegus tanacetifolia (Lam.) Pers. - (:unkn) unknown (UNIV AGR SCI & VETERINARY MED CLUJ-NAPOCA, 2015)
In this study, the development of male reproductive organ was analysed in Crataegus tanacetifolia (Lam.) Pers., endemic to Turkey. Androecium is composed of 20 stamens which are attached at the base of the filaments. The anther wall formation follows the dicotyledonous type. The undifferentiated anther is ovoid-shaped, and the differentiation starts with the appearance of archesporial cells. Mature anthers are dorsifix and tetrasporangiate. The anther wall is composed of an epidermis, endothecium, two or three rows of middle layers and secretory tapetum. Endothecial cells show fibrous thickening. Tapetum is characterized by enlarged secretory types with binucleate cells, which presented an intense reaction with regard to proteins, insoluble polysaccharides and lipids. Features of chromatin condensation and nucleus disorders identified with the application of DAPI (4',6-diaminido-2-phenylindole) point out programmed cell death. Epidermal and endothecial layers remain intact until anther dehiscence; however, middle layer and tapetum disappear during development. At the end of regular meiotic division, tetrahedral microspore tetrads are formed. Pollen grains are tricolparatae, tectate and sphaeroidea. Exine is made up of lipoidal substances and proteins, but the intine includes insoluble polysaccharides. Further, cytoplasm of pollen grains are rich in proteins, lipids and insoluble polysaccharides.
Keywords: anther ontogeny; anther wall; microsporogenesis; Rosaceae; POLLEN MORPHOLOGY; ROSACEAE; TAPETUM; CELLS; MICROSPOROGENESIS; ANGIOSPERMS; PHYLOGENY; ANTHERS; SURFACE